Correction of Non-Uniform illumination for Biological Images Using Morphological Operation Assessing with Statistical Features Quality. - Hussain, Layla H. abaas; alamry, Amel H.Abbas (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Non Uniform Illumination biological image often leads to diminish structures and inhomogeneous intensities of the image. Algorithm has been proposed using Morphological Operations different types of structuring elements including (dick, line, square and ball) with the same parameters of (15).To correct the non-uniform illumination and enhancement biological images, the non-uniform background illumination have been removed from image, using (contrast adjustment, histogram equalization and adaptive histogram equalization). The used basic approach to extract the statistical features values from gray level of co-occurrence matrices (GLCM) can show the typical values for features content of biological images that can be in form of shape or specific features. In this research, the application of gray level cooccurrence matrix (GLCM) statistical features correlation, contras, energy and Homogeneity have presented these features which have high accuracy and efficiently. The color biological images had been used taken which is from microbiology laboratory at the Biological Department College of Science Al-MustansiriyhUniversity. The algorithms have been applied on ten different biological color images, in this work only two images have been displayed.